2018
DOI: 10.1186/s13052-018-0575-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of neonatal sepsis: has-miR-150 targeting BCL11B functions in disease progression

Abstract: BackgroundNeonatal sepsis is an inflammatory systemic syndrome, which is a major cause of morbidity and mortality in premature infants. We analyzed the expression profile data of E-MTAB-4785 to reveal the pathogenesis of the disease.MethodsThe expression profile dataset E-MTAB-4785, which contained 17 sepsis samples and 19 normal samples, was obtained from the ArrayExpress database. The differentially expressed genes (DEGs) were analyzed by the Bayesian testing method in limma package. Based on the DAVID onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…MAPK14 has already been identified as a key gene and potential therapeutic target in neonatal sepsis. 52 , 53 Deficiency of MAPK14 in macrophages protects mice from lipopolysaccharide (LPS)-induced sepsis. 54 FGR proto-oncogene (FGR) is a Src family kinase that is expressed in innate immune cells, including macrophages and granulocytes, and is considered a major signaling molecule downstream of many immune cell receptors.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK14 has already been identified as a key gene and potential therapeutic target in neonatal sepsis. 52 , 53 Deficiency of MAPK14 in macrophages protects mice from lipopolysaccharide (LPS)-induced sepsis. 54 FGR proto-oncogene (FGR) is a Src family kinase that is expressed in innate immune cells, including macrophages and granulocytes, and is considered a major signaling molecule downstream of many immune cell receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 17 ] identified candidate biomarkers (Icam1 and Socs3) for sepsis from one GEO datasets by performing DEG, gene functional enrichment, and PPI network analyses, and validated their results with RT-qPCR. Huang et al [ 18 ] identified hub genes (MAPK14, ZAP70, and TSPO) and miRNA related to sepsis progression from 1 dataset of E-MTAB-4765 by developing an integrated method including DEG screen, pathway analysis, gene annotations, PPI networks, and regulatory network construction. These studies also identified some hub-genes of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, T-cells are inadequately supervised by the thymus microenvironment, exhibit decreased apoptosis and cannot differentiate into Th2 T-cells (33). Huang et al (34) reported that the downregulation of Zap70 accelerated disease progression of neonatal sepsis. IKBKB encodes IKB kinase 2 (also known as IKKβ /IKK2), a component of the nuclear factor-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%